THE INFLUENCE OF WORK DISCIPLINE ON EMPLOYEE PERFORMANCE IN THE TELLU LIMPOE DISTRICT OFFICE - Fila Mappe; Amrizal Salida; Ari Ayu (Universitas Ichsan Sidenreng Rappang, 2025)
Human resources as the main element in an agency have a very large role in determining the success and achievement of the company's goals that have been set. Many factors influence performance to achieve the standards expected by the company, one of the most influential factors is the discipline factor. Indiscipline in time that dominates performance does not comply with agency standards and regulations so that it has an impact on increasing and decreasing employee performance. This study aims to determine whether there is an influence between work discipline and employee performance at the Tellu Limpoe District Office. The population in this study was 30 employees at the Tellu Limpoe District Office, and the sample was determined purposively. The research method used in this study is a quantitative descriptive method. Based on the results of the analysis that has been carried out, it shows that the work discipline variable has a positive effect on employee performance at the Tellu Limpoe District Office. Based on tcount (6.262) ≥ ttable (2.048), it can be concluded that work discipline contributes greatly to employee performance and can be said to be significant from the analysis that has been carried out on employees at the Tellu Limpoe District Office.